ANALISIS YURIDIS TERHADAP HAK WARIS ANAK LUAR KAWIN PASCA PUTUSAN MK NO. 46/PUI-VIII/2010 - Hasanah, Amelia Nur; Ramadhoni, Moh Zainullah; Dafira, Lucky (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
The Constitutional Court Decision No. 46/PUU-VIII/2010 has brought significant legal reforms regarding the recognition of children born outside of marriage. Previously, such children were legally affiliated only with their mothers, as stipulated in Article 43 paragraph (1) of Law Number 1 of 1974 on Marriage. Through this ruling, the Court affirmed that children born out of wedlock who can be proven to have a biological relationship with their father are also entitled to legal civil recognition, including inheritance rights. This study aims to examine the legal implications of the decision on inheritance rights of children born out of wedlock and its practical implementation within the Indonesian legal system. Using a normative juridical approach, the research analyzes secondary data through literature reviews of statutory regulations, legal doctrines, and relevant court decisions. The findings indicate that although the Constitutional Court’s ruling provides greater justice for out-of-wedlock children to claim inheritance rights, its implementation faces obstacles, particularly in proving biological relationships and reconciling with religious norms. Therefore, legal harmonization and a comprehensive understanding by law enforcement officials are needed to ensure the equitable and just fulfillment of the rights of children born out of wedlock